Sistem Informasi Feeder Data Kependudukan berbasis Mobile - Irvan Yohanes Lim; Emirensiana Eba; Alija Remigis Bere; Maria Putu Sugiati Keraf; Kristian Karpus Paulino; Emanuel Fernandez; Paskalis Andrianus Nani (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
The uneven internet network in East Nusa Tenggara Province has resulted in a web-based population administration system application becoming less effective in the process of directly filling in population data in people's homes. The purpose of this research is to develop a system that can fill in population data offline and synchronize it with the server periodically. The method used in the development process of this system is extreme programming, with stages consisting of planning, design, coding, and testing. In the planning stage, interviews are conducted to gather user stories. Prioritization of user stories is arranged in the design stage. In addition, the system architecture design is also created at this stage. In the coding stage, the application is developed, and unit tests are made to reduce defects in the application. In the testing stage, a synchronization simulation is performed between the application and the server using dummy data up to 5000 records per transaction. The results of this study show that the application can fill in data offline and synchronize data with the server with a success rate of 100%. This mobile-based population data feeder application can assist local and provincial governments in obtaining valid information about the population in their areas, thus becoming a decision-support tool for various things, including social assistance and temporary voter list data for the upcoming regional, legislative, and presidential elections.